Performance e contradição social na festa dos Lambe Sujos e Caboclinhos em Laranjeiras/SE - Santos, Vanessa Regina dos (2016)
This paper seeks to understand the feast of Lambe dirty versus Caboclinhos leaving the party concept and what this engaging , as jokes , routine breaks , social and historical continuity , legitimacy , taking as focus performance in the theatrical aspect, bringing a theoretical and methodological implementing some ideas that emerged in the middle of the master research. The object described is the festival that takes place for more than nine decades in the city of Orange in Sergipe which its plot is the struggle between blacks and Indians , dirty Lambe and Caboclinhos respectively , however within this narrative exists indirectly white , represented by bush captains as intercessors of relations with indigenous. So the story presented during the second weekend of October is the confrontational battle of the three ethnic groups, which unfolds with clashes and a number of symbols and meanings to be described in this work . For the development of this research will use several authors from the most classic to the most contemporary, and it comes to an ethnography, field research and applications of semi-structured questionnaires in open and closed questions that will be of great justification shall be used to continue the analysis informal and formal conversations through testimonials and historiographical sources for the composition of the historical and geographical context of the city. The advancement of research linked to the experience and the theoretical basis will lead me to structure the synchronic and diachronic thesis to lead to right conclusions about which involve actions presented, coming to the realization as the parties reflect the social dilemmas experienced and remembered through these.